Rethinking Value Chains : Tackling the Challenges of Global Capitalism - Palpacuer, Florence (Book collections on Project MUSE., 2021)
EPUB and EPDF available Open Access under CC-BY-NC-ND licence. This original volume brings together academics and activists from Europe to think creatively about the social and environmental imbalances of global production and how to reform the current economic system.